The Impact Of The Existence Of Asta Sayyid Yusuf Religious Tourism On Improving The Economy Of The Talango Village Community - Qurratul Aini; Dony Burhan Noor Hasan; Enni Endriyati (JOURNAL OF SHARIA ECONOMICS, 2023)
This research discusses the impact of the existence of Asta Sayyid Yusuf religious tourism on improving the economy of the people of Talango Village, Sumenep Regency. Asta Sayyid Yusuf's religious tourism is increasingly attracting more and more visitors and is becoming increasingly well known by the people of Madura Island and people outside Madura Island, which of course has a positive impact on improving the community's economy. This is one of the reasons researchers are interested in researching in more depth the impact of the existence of Asta Sayyid Yusuf religious tourism on improving the economy of the people of Talango Village. The research method used in this research is a descriptive qualitative approach. The data used in this research are primary data and secondary data, then data collection techniques are carried out by means of interviews, observation and documentation. The data analysis stage was carried out by means of data reduction, data presentation, and drawing conclusions. The aim of this research is to determine the impact of the existence of Asta Sayyid Yusuf religious tourism on improving the economy of the Talango Village community. Based on the research results, the existence of Asta Sayyid Yusuf religious tourism has had a positive impact on the economy of local communities, especially those around the Asta Sayyid Yusuf religious tourism area. One of the impacts that occurs is an increase in people's income, business opportunities and employment opportunities for the community